Scatter imaging with super-memory effect based on adaptive β-parameter hybrid input-output algorithm-assisted estimation of point spread function. (1st October 2022) - Cao, Chaowei; Cui, Guangmang; Zhao, Jufeng; He, Bintao; Zhu, Liyao
Abstract: It is of great significance to realize the imaging of the target behind the scattering medium, which is often limited by the optical memory effect range. In this paper, a non-invasive super-memory effect scattering imaging method based on adaptive β -parameter hybrid input-output (APHIO) algorithm-assisted point spread function (PSF) estimation is proposed. An iterative algorithm APHIO is designed to use the speckle autocorrelation region to constrain the iterative region and optimize the value of the parameter β in the traditional HIO algorithm. Besides, the estimated PSF of the imaging system is combined with a new scanning method to better reconstruct the target object with super-memory effect range. The results show that the APHIO algorithm has the characteristics of faster convergence and more stable reconstruction quality than the traditional HIO algorithm. The overall imaging framework has a good performance in the reconstruction efficiency of the target with super-memory effect range.